A geografia eleitoral do Estado do Tocantins: - Santos, Robson Francisco Barros dos (Universidade Federal do Tocantins, 2023)
The Electoral Geography is little studied in the Brazilian geographic science and it is also present in the Political Geography area. In this research, I tried to give contribution to this theme that is so important nowadays. In this research I analyzed the Electoral Geography of Tocantins State, state that is the newest of the federation with all its mishaps. The analysis was conducted using data collected on the site of Supreme Electoral Tribunal (TSE) and on the website of Regional Electoral Court (TRE). The electoral data were for mayors corresponding to the pleas in 1996, 2000, 2004, 2008 and 2012 in each county of Tocantins and governors corresponding to the pleas in 1994, 1998, 2002, 2006, 2010 and 2014. The data were based on the theoretical framework proposed to analyze the data. And through data and theoretical reference I elaborated the maps and the final outcomes of the research findings, thus I built a theoretical framework about the electoral geography and the policy of Tocantins state.